2020
DOI: 10.1152/ajpheart.00415.2020
|View full text |Cite
|
Sign up to set email alerts
|

p38δ genetic ablation protects female mice from anthracycline cardiotoxicity

Abstract: BACKGROUND: The efficacy of an anthracycline antibiotic doxorubicin (DOX) as a chemotherapeutic agent is limited by dose-dependent cardiotoxicity. DOX is associated with activation of intracellular stress signaling pathways including p38 MAPKs. While previous studies have implicated p38 MAPK signaling in DOX-induced cardiac injury, the roles of the individual p38 isoforms, specifically, of the alternative isoforms p38g and p38d, remain uncharacterized. OBJECTIVES: To determine the potential cardioprotective ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
1
12
1
Order By: Relevance
“…Beyond 2 min, mice became stressed and motion artifacts were introduced into the signals. Mice were then anesthetized using isoflurane (1-2.5%, 1 ml/min oxygen) using an EZ anesthesia machine to maintain a heart rate of ~400 bpm (for echocardiography simultaneously performed and previously published (George et al, 2020)). Once unconscious, mice were transferred to the mouse platform of a Vevo 3100 ultrasound machine (FUJIFILM VisualSonics) and anesthesia administration was continued via a nose cone.…”
Section: Micementioning
confidence: 99%
See 3 more Smart Citations
“…Beyond 2 min, mice became stressed and motion artifacts were introduced into the signals. Mice were then anesthetized using isoflurane (1-2.5%, 1 ml/min oxygen) using an EZ anesthesia machine to maintain a heart rate of ~400 bpm (for echocardiography simultaneously performed and previously published (George et al, 2020)). Once unconscious, mice were transferred to the mouse platform of a Vevo 3100 ultrasound machine (FUJIFILM VisualSonics) and anesthesia administration was continued via a nose cone.…”
Section: Micementioning
confidence: 99%
“…Currently, echocardiography is the method of choice in the clinical setting and ejection fraction is the preferred metric (Meijers & Moslehi, 2019;Perez et al, 2019). However, in our previous study, we demonstrated the role of preserved ejection fraction in some subjects as a potential cause of undiagnosed DOX-induced cardiotoxicity (George et al, 2020). Electrocardiography (ECG) is another method to detect DOX cardiotoxicity in patients, however, this technique too has its limitations.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…And we selected the coronal sections of the heart from the base, mid and apex regions. (George et al, 2020) Coronal section was cut (thickness, 7 lm) and stained with picros sirius red (1:1,000 dilution, Sigma) for calculation of the interstitial collagen fraction (female control, n ¼ 7; female EAE, n ¼ 7; male control, n ¼ 6; male EAE, n ¼ 6). (Zhou et al, 2018) Hematoxylin and eosin staining was used for measurement of cardiomyocyte cross-sectional area (female control, n ¼ 9; female EAE, n ¼ 8; male control, n ¼ 10; male EAE, n ¼ 7).…”
Section: Measurement Of Heart Fibrosis and Hypertrophymentioning
confidence: 99%